Linguacultural Features of Command and Interrogative Constructions in Uzbek and English - Ishanjanova Munosib; Ahmadaliyeva Madina (Zien Journals, 2023)
This article analyzes the linguistic and cultural characteristics of command and interrogative constructions in Uzbek and English. The use of politeness markers, modal verbs, indirect questions, and tag questions reveals the cultural differences in the importance of politeness, directness, and indirectness. Understanding these linguistic and cultural differences is crucial for effective cross-cultural communication and building cultural competence
Keywords: Uzbek language; English language; command constructions